2018
DOI: 10.1075/slcs.199.03ada
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic and morphological focus marking in Ixcatec (Otomanguean)

Abstract: This paper presents the first description of the expression of focus in Ixcatec, a nearly extinct language of Mexico. The study is based on experimental tasks carried out with the last three fluent speakers of Ixcatec. Prosodic analysis shows that in Ixcatec, a language with three lexical tones, contrastive focus is associated with raised F0, lack of focus is marked through lowered F0 and decreased duration, and corrective focus is signaled through various speakerspecific means. Finally, this study shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In an information structure phonetic study in Ixcatec, real-life objects were shown in a first session (e.g., fruits); photographs of these objects were shown in a second session. This combination allowed for enough repetitions while avoiding a habituation process that could interfere with information structure status (Adamou et al 2018).…”
Section: Semi-experimental Tasksmentioning
confidence: 99%
See 1 more Smart Citation
“…In an information structure phonetic study in Ixcatec, real-life objects were shown in a first session (e.g., fruits); photographs of these objects were shown in a second session. This combination allowed for enough repetitions while avoiding a habituation process that could interfere with information structure status (Adamou et al 2018).…”
Section: Semi-experimental Tasksmentioning
confidence: 99%
“…Regarding visual stimuli, it is best to use coloured photographs rather than black and white line drawings given that little-educated participants have difficulties recognizing the latter (Reis et al 2006). One can either use existing visual stimuli or create their own, culturally-adapted stimuli (see Borja et al 2016;Adamou 2017;Adamou et al 2018;Calderón et al 2019). To build an experiment, a free open source experiment builder is Open Sesame (Mathôt et al 2012).…”
Section: Step 4 Prepare Your Stimuli and Build Your Experimentsmentioning
confidence: 99%